AGILE GOVERNANCE SEBAGAI KERANGKA REFORMASI BIROKRASI: ANALISIS KONSEPTUAL ATAS KESIAPAN TATA KELOLA DIGITAL PEMERINTAH KABUPATEN BANYUWANGI - Ahmad Maulana Iqbal Iqbal; Muhammad Izwan Aiman Izwan; Akbar Maulana Akbar (BRIN (Badan Riset dan Inovasi Nasional), 2026)
Digital transformation in government requires adaptive and responsive governance frameworks to meet the dynamics of change. This article conceptually analyzes the application of Agile Governance as a bureaucratic reform framework, using Banyuwangi Regency Government as a reference context. Through a systematic literature analysis approach and New Public Governance theoretical framework, this study maps the dimensions of local government digital readiness including institutional capacity, technology infrastructure, human resources, and public participation. The analysis reveals that Banyuwangi has initiated various digital innovations aligned with Agile Governance principles, such as data-driven policy iteration, cross-sector collaboration, and public information transparency. However, significant implementation gaps exist in areas of data standardization, system interoperability, and digital human resource competency. This article recommends a multi-layer Agile Governance model integrating technical, organizational, and socio-cultural dimensions as an alternative framework for sustainable digital-based bureaucratic reform.